How Can We Study Children's/Youth's Out of School Experiences to Inform Classroom Practices?. (November 2020) - McCarthey, Sarah; Duke, Nell K.; Bloome, David; Faust, Sara; García-Sánchez, Inmaculada M.; Stornaiuolo, Amy; Alvermann, Donna
The collection of papers represented in the Integrative Research Review responds to the question: How can we study children's/youth's out of school experiences to inform classroom practices? Using a variety of lenses to address the question, the authors consider how to understand, respond to, and serve children and youth in a variety of contexts. Duke explores a quasi-experimental design showing the potential impact on student achievement and motivation in schools that incorporate literacy practices from children's lives outside of school compared to the traditional curriculum. Bloome and Faust take a philosophical approach to explore the languaging of the relationship between students' out-of-school lives and classroom practices and its implications for the construction of personhood by examining one classroom event from a microethnographic discourse analysis perspective. García-Sánchez highlights the methodological features that allow linguistic anthropologists to make visible the agentive and innovative character of immigrant children's communicative practices in a variety of learning situations. Drawing on the transliteracies approach, Stornaiuolo considers work with a group of young people to study multimodal composing and the development of school makerspaces in a 6-year partnership project with a local innovation high school. Alvermann discusses the papers, pointing out the affordances and challenges of each perspective.